Sensitivity analysis of generalized variational inequalities - Mukherjee, R.N.; Verma, H.L. (My University, 1992)
Dafermos studied the sensitivity properties of the solutions of a variational inequality with regard to continuity and differentiability of such solutions with respect to a parameter λ. In the present paper we extend this analysis for a generalized variational inequality of the type introduced by Noor of which the variational inequality of Dafermos is a particular case. Our results are such that they automatically extend the regularity properties of solutions with respect to a parameter λ when the variational inequality is treated on a Hilbert space.
Keywords: variational inequalities